The Implementation Of Kaizen To Improve After Sales Service In General Repair (GR) Workshop Of PT. Nasmoco Kaligawe Semarang - Ghofur, Muhammad Abdul; Triyani, Dian (Economics and Business Solutions Journal, 2019)
This study aims to find out the application of kaizen, the impact felt by the employees in applying kaizen and the customers feedback on kaizen products that have been implemented to improve the after sales service of PT Nasmoco Kaligawe Semarang general repair workshop. This study was conducted by using qualitative research method in analyzing the application of kaizen.The method of data collection was carried out by conducting observation and documentation. The data collection method to find out the impact that employees feel and the customers feedback on kaizen products that have been implemented used the direct interview method with 4 employees who have applied kaizen and 5 customers who have experienced kaizen products. The results of this study indicate that the application of kaizen in PT Nasmoco Kaligawe Semarang general repair workshop has run well. The impact felt by the employees is also good, the employees become more satisfied at work. The feedback given by the customers for kaizenthat has been conducted is very good. Kaizen makes the customers more comfortable and satisfied with the services provided to themselves and their vehicles.